Enhanced photochemical production of reactive intermediates at the wetland soil-water interface. (1st September 2022) - Wu, Binbin; Zhou, Chong; Zhao, Guoqiang; Wang, Jingyi; Dai, Hengyi; Liu, Tian; Zheng, Xiaoshan; Chen, Baoliang; Chu, Chiheng
Highlights: Soil-water interface (SWI) was an unrecognized hotspot for PPRI photoproduction. Photochemical OH production at SWI was enhanced by one order of magnitude. Nationwide surveys demonstrated SWI as ubiquitous PPRI hotspot in wetlands. Elevated SWI PPRI production accelerated nutrient and pollutant transformation. Abstract: Photochemically produced reactive intermediates (PPRIs) formed by sunlight-irradiation of natural photosensitizers play critical roles in accelerating biogeochemical cycles on earth surface. Existing PPRI studies mostly focus on bulk phase reactions (e.g., bulk water), with PPRI processes at the environmental interfaces largely unexplored. Here, we report the wetland soil-water interface (SWI) as a widespread but previously unappreciated hotspot for PPRI productions. Massive productions of four important PPRI species (i.e., triplet-state excited organic matter ( 3 OM*), singlet oxygen ( 1 O2 ), hydrogen peroxide (H2 O2 ), and hydroxyl radical ( OH)) were observed at the SWI. All four PPRI species exhibited higher productions at the SWI than those in bulk water, where OH production was largely elevated by up to one order of magnitude. The enhanced PPRI productions at the SWI were caused by intensified photon absorption and vibrant Fe-mediated redox processes, where the light absorption by less- or non-photoactive soil substances partially offset the enhancement on PPRI productions. Nationwide wetland investigations demonstrate that the SWI was a ubiquitous hotspot for PPRI productions. Simulations on PPRIs-mediated reactions suggest that the enhanced PPRI productions could greatly affect the kinetics and transformation pathways of nutrients and pollutants. Given that the SWI also acts a hotspot for nutrient and pollutant accumulation, incorporating the SWI enhanced PPRI productions into biogeochemical process assessments is pivotal for advancing our understandings on the element cycles and pollutant dynamics in wetlands. Graphical Abstract: Image, graphical abstract